Factors related to the event of hypercolesterolemia in Dr. Pirngadi Hospital Medan Year 2018 - Panjaitan, Melda; Aritonang, Evawany; Fentiana, Nina (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Hypercholesteromia is a condition when the concentration of cholesterol in the blood exceeds the normal limit. Hypercholesterolemia is a metabolic disorder that occurs primarily or secondary due to various diseases that can contribute to various types of diseases, especially cardiovascular disease. Hypercoleterolemia is closely related to hyperlipidemia and hyperlipoproteinemia. The purpose of this study was to determine the magnitude of the risk factors associated with the incidence of hypercholesterolemia in RSUD Dr Pirngadi Medan City in 2018. This type of research was an analytical observation study, with a cross sectional design. From the calculation of the sample above, it can be concluded that the number of samples in this study were 48 respondents. Samples were taken by using accidental sampling technique, namely outpatients and treatment for internal disease who were diagnosed with hypercholesterolemia in Dr Pirngadi Hospital, Medan. The results showed there was a relationship between smoking habits and the incidence of hypercholesterolemia. There is no association with obesity with the incidence of hypercholesterolemia. There is a relationship of physical activity with the incidence of hypercholesterolemia. Smoking is a factor that most influences the incidence of hypercholesterolemia in Dr Pirngadi Hospital in 2018. It is expected that health workers can provide counseling to patients who experience hypercholesterolemia especially for patients who have not experienced hypercholesterolemia so that an increase in HDL in the body can prevented early